(untitled) (Sains Humanika, 2021)
The purpose of this study is to evaluate the doctors-patients communication style and their information seeking practiced among doctors under training or junior doctors in Malaysian hospital. Two types of communication styles evaluated are doctor centered and patient centered communication. Meanwhile, elements of information seeking practice evaluated are exploration of the reason for encounter, history taking, concrete solutions, structuring the interview, interpersonal skills and communicative skills. These six elements were categorized into interview skills and process skills. This information seeking skills have been derived from meta-analysis conducted by Stewart and Roter (1989). We combined the doctors-patients communication style and information seeking practice to develop a model based on four quadrants namely doctors-interview, doctors-process, patient-interview and patient-process. The subjects for this research are doctors under training or junior doctors in Malaysia. This explorative research distributed a set of questionnaires in order to collect data for analysis. The result show that the doctors under training or junior doctors tend to practice doctor-centered styles compare to patient-centered. Meanwhile, most of them demonstrate all the information seeking practice at a high level. Based on four quadrants developed by researcher, research shows that the doctors mostly categorized in doctor-centered communication style and interview information-seeking skills. We suggested that doctors should be more patient-oriented rather than doctor oriented. We also suggested the model that we developed can be used as a model of communication pattern of the doctors and can be used for future research.